Kajian Penggunaan Pupuk Organik pada Sistem Usahatani Bawang Merah di Serang Banten - Purba, Resmayeti (Universitas Muhammadiyah Yogyakarta, 2016)
Yield of shallot bulbs in Banten still low because famers do not use organic fertilizers. This study aims to study the effectiveness of organic fertilizers combined with inorganic fertilizer on the growth and yield of shallot. This study was conducted in farmersâ fields in Sawahluhur village, district Kasemen, Serang. Studies used a randomized complete block design consisting of 5 treatments and 4 replications. The varieties used are Bima. The results showed that the use of organic fertilizers in combination with inorganic fertilizers provide a good influence on the growth and yield of shallots. The use of organic artificial fertilizer 5.000 kg//ha + Urea 100 kg/ha+ SP-36 200 kg/ha + 300 kg/ha NPK Phonska resulted in higher yield of tubers and profits than without organic fertilizer on shallots farming.